Difficulties in Diagnosing Dust Bronchitis in the Practice of a Resident - Nosirova Dildora Erkinovna (American Journal of Bioscience and Clinical Integrity, 2024)
Scientific and technological progress, the introduction of mechanization and automation in production processes, modernization of equipment, rationalization of sanitary devices have caused the disappearance or sharp change of occupational harmful factors in most enterprises of our country. The article considers the importance of timely diagnosis, differential diagnosis, therapeutic and preventive factors in the diagnosis of dust bronchitis developed under the influence of dust.